Analisis Sistem Dinding Partisi untuk Kantor yang Efisien dan Berkelanjutan di Jakarta - Fendy Eka Febriyatna; Muhammad Siam Priyono Nugroho (Prosiding (SIAR) Seminar Ilmiah Arsitektur, 2026)
This research develops a partition wall system for the renovation of a structural consultant office in Jakarta that faces land limitations and high renovation costs. The system optimizes space efficiency, spatial flexibility, and sustainability by recycling existing coconut coir-reinforced gypsum panels as an economical acoustic performance enhancing material. The results show that partition systems integrated with organic local acoustic materials can improve spatial efficiency to be more flexible, reduce construction waste and reduce the carbon footprint of buildings, support the circular economy and can be applied to respond to business dynamics and challenges of dense urban environments such as Jakarta.